2015
DOI: 10.1299/jamdsm.2015jamdsm0057
|View full text |Cite
|
Sign up to set email alerts
|

Machinability analysis on helical milling of carbon fiber reinforced polymer

Abstract: In the helical milling process, a rotating tool traverses a helical trajectory to generate a hole. In order to investigate the cutting state in helical milling of carbon fiber reinforced polymer(CFRP), experiments were conducted with unidirectional and multidirectional laminates. Cutting forces, tool wear state and hole quality were discussed respectively. The effect of cutting parameters on the cutting forces was first presented, then the influence of different workpiece material on the cutting forces was sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In a mold manufacturing it is estimated that 65% of the costs are due to finishing and semi-finishing processes by machining [2,3]. Between these processes, hole-making spends from 25% to 50% of the cycle time and 33% of the total number of operations, requesting reliability due to the high added value to the part being processed [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a mold manufacturing it is estimated that 65% of the costs are due to finishing and semi-finishing processes by machining [2,3]. Between these processes, hole-making spends from 25% to 50% of the cycle time and 33% of the total number of operations, requesting reliability due to the high added value to the part being processed [4,5].…”
mentioning
confidence: 99%
“…The maximum axial depth of cut (ap * ) is mathematically dependent of the feed velocities components in axial and tangential directions [14]. Firstly, the helix angle (α) can be expressed through Equation 5 and, subsequently, ap * , which is the helical pitch, in [mm/rev], is calculated through the Equation 6, considering the helix angle and the length of the circular path (π×Dh). By manipulating this expression considering Equations 1-4, ap * may be defined with regard to fza and fzt to understand the effect of these portions of cut related to axial and peripheral cut, respectively [16].…”
mentioning
confidence: 99%
“…They stated a similar conclusion for the aluminum alloy, where the force was 50% smaller using a coated tool in comparison to drilling with a non-coated tool. Wang [ 34 ] showed that the cutting force increases with increasing feed rate but depends on the cutting speed. Examining the results of cutting forces, it can be noted that for both types of tools for f z = 0.04 mm/min and for the non-coated tool at f z = 0.12 mm/min, the cutting forces increased with an increase in the cutting speed.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the best machining quality was obtained with the combination of high cutting speed, low feed rate and effective chip thickness. In another study, Wang et al [23] worked on the delamination damage occurring during the unidirectional and multidirectional helical milling of CFRP composites, and reported that delamination was observed on the machined edges, arising from tool wear and resulting in inadequate machining quality. They found that adequate machining performance was obtained with a sharp cutting tool, which also prevented delamination failure.…”
Section: Introductionmentioning
confidence: 99%